2020
DOI: 10.1159/000505448
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Clinicopathologic Features and Surgical Treatment of Premenopausal Breast Cancer across Italy and China: Report from a Medical Exchange Program

Abstract: <b><i>Background:</i></b> This study investigated the differences in clinicopathologic features and surgical treatment between an Italian and a Chinese cohort of premenopausal women with breast cancer, and highlighted the potential advantages of international medical exchange projects. <b><i>Methods:</i></b> Premenopausal women who underwent surgical treatment between 2012 and 2016 at one Italian and one Chinese institution participating in a medical exchange pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Our research revealed that clinical profile and tumor characteristics varied significantly between breast cancer patients in Italy and Vietnam. The variations in presenta-tion, clinicopathological profiles, biomarkers, and molecular subtypes might be attributed to the differences in race, lifestyle, living environment, and late diagnosis expression [3,17,18]. Our findings from this study are roughly in accord with those reported in Vietnam and Italy, respectively [6,9,[18][19][20][21].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our research revealed that clinical profile and tumor characteristics varied significantly between breast cancer patients in Italy and Vietnam. The variations in presenta-tion, clinicopathological profiles, biomarkers, and molecular subtypes might be attributed to the differences in race, lifestyle, living environment, and late diagnosis expression [3,17,18]. Our findings from this study are roughly in accord with those reported in Vietnam and Italy, respectively [6,9,[18][19][20][21].…”
Section: Discussionsupporting
confidence: 86%
“…Lack of knowledge, being too busy, staying far from treatment facilities, bearing high treatment costs, and not receiving good quality healthcare service, ... might be some reasons leading to the delay in the treatment [10]. In addition, the participation rate in breast cancer screening programs in Vietnam and other Asian countries was lower compared to Western countries [3,18]. There is not enough information provided about screening processes and how screening services are integrated with other areas of the health system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation